Empang Parit as Silvofishery Model to Support Conserving Mangrove and Increasing Economic Benefit of Social Community - Endang Hilmi; Setiyo Nugroho; Eming Sudiana (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2021)
Mangrove, estuary and lagoon ecosystem can be used as the aquatic organism habitat. These ecosystems also have good suitability to support activity of silvofishery system. Empang parit as a model of silvofishery using the integrating between the conservation activity of mangrove and aquatic ecosystem with increasing of benefit income for fisherman. This research aimed to analyze the model and pattern of empang parit, environment factor of empang parit and benefit cost analysis of empang parit. The research used vegetation analysis, water quality analysis, cash flow analysis, satellite image analysis, and geographical information analysis. The research explained that empang parit required water temperatur between 29 – 32.6oC, water brightnes between 30 – 60 cm, water salinity between 15 -32 ppt, pH between 7 – 81 and dissolve oxygen between 3.9 – 8.3 mg/L.The empang parit also need Bruguiera gymnorrhiza, Heritiera littoralis and Excoecaria agallocha, Rhizophora mucronata and Rhizophora apiculate to cover empang parit system. And empang parit gave postive economic value based on value of NPV between 2.754.703–3.871.542 IDR, IRR between 21–48 and R/C between 2.26–2.32.Keywords : Empang parit; silvofishery system; economic valuation; water quality; mangrove coverage